MENGAJARKAN SELF INTRODUCTION DENGAN MENGGUNAKAN METODE PERMAINAN - Hartatya Novika; Dewi Rosaria (JURNAL PENGABDIAN AL-IKHLAS UNIVERSITAS ISLAM KALIMANTAN MUHAMMAD ARSYAD AL BANJARY, 2017)
This community service activity was in the form of teaching self introduction by using games method and the target audience is primary school age children at Semangat Dalam village RT.31Handil Bhakti. The objectiveis to teach self introduction to primary school age children by using games method. This activity used games method. The result of this activity isabout 87,5% of 16 primary school age children (6-12 years of age) were able to introduce themselves in English after team taught them by using games method in particular by singing songs related to the material.They became more confident to introduce themselves by using English in front of their friends.